The employee productivity associated with work position and musculoskeletal disorders among tailors in the PT. Uluwatu Garment - Ni Wayan Sri Wahyuni Sri Wahyuni; Ari Wibawa; Ni Wayan Tianing; Agung Wiwiek Indrayani (Bali Anatomy Journal, 2021)
Background: Musculoskeletal disorders are known to be one of the factors that affect the level of productivity among employees,especially tailors. Aim: This study aims to determine the correlation between the work position and musculoskeletal disorders which affect productivity among tailors. Methods: The cross-sectional analytical study was conducted on 65 samples. The data were collected by using the quick eksposure check questionnaire (QEC) and the nordic body map (NBM) questionnaire. The results were then analysed using the normality test by the Kolmogorov-Smirnov test. The correlation analysis and regression analysis was applied to determine the extent of the relationship between the two variables. Results: The data from the QEC questionnaire showed the ergonomic position of the sample was in the safe category (53.8%). The NBM questionnaire data found the samples’ complaints of musculoskeletal disorders are in the low category (52.3%). The results of the normality test showed p <0.05, meanwhile the correlation test showed p> 0.05. The linear regression test showed the result of the correlation coefficient for musculoskeletal disorders -0.174. This research concludes that partially, musculoskeletal disorders affect work productivity. The level of musculoskeletal disorders was low because it was impacted by workload weight and posture balance. Skills and work experience also impacted the level of work productivity. Conclusion: The conclusion of this study is there was no significant correlation between the work position and musculoskeletal disorders with work productivity for tailors in PT. Uluwatu.